Lung ultrasound findings in Mexican patients with SAR S-CoV-2 infection - Ivan Ilescas-MartÃnez; Luis F. Paredes-FernÃ¡ndez; Lilian S. RamÃrez-Serrano; Adriana Clemente-Herrera; Rodrigo Saavedra-Luna; Salvador Ãvila-Ruiz (Revista de Educación e Investigación en Emergencias, 2022)
Introduction: On December 2019, a new disease reported by an unknown pathogen was reported, which turned out to be a new variant of coronavirus, now called SARS-CoV-2. This new disease had a very rapid global spread, causing multiple deaths, and which led to putting the entire world on health alert. In patients who have this disease, some authors suggested the use of lung ultrasound (LUS) for its early recognition. Objective: Describe the findings of LUS in Mexican patients with COVID 19. Methods: We evaluated the findings of LUS in 25 patients admitted to the General Hospital Enrique Cabrera, Mexico, with a diagnosis confirmed by reverse transcriptase-polymerase chain reaction (RT-PCR) of SARS-CoV-2. Results: This small retrospective study suggests that artifacts such as glass rockets with or without the Birolleau variant (White lung), confluent B-lines, thick irregular pleural lines, and variable size (subpleural) consolidations are typical findings of LUS in patients with COVID-19 pneumonia. Conclusions: The presence of these findings is useful when evaluating patients with suspected COVID-19. In resource-limited and austere settings where chest radiography, CT, and RT-PCR are not available or the response time is long, LUS performed by trained personnel can be an aid in the diagnosis of COVID-19.